Use of Assertive Training Techniques to Improve Adolescents’ Self-Conﬁdence in High School Students of Class VIII - Arista , Dea Mega; Sanyata , Sigit (KnE Social Sciences, 2019)
This research aimed to find out the improvement of adolescents’ self-confidence through the use of assertive training method in high school students. It used action research by determining the research subjects based on purposive sampling techniques in 5 students of class VIII. The research instrument was a scale of self-confidence and observation guidance. The assertive training method was performed in one cycle which had been divided into four activities. This research used statistical analysis techniques of non-parametric by using Wilcoxon Signed Rank Test. The results indicated that: (1) the initial condition of self-confidence in high school students of class VIIIB SMP Muhammadiyah Pakem was individually low. The condition was proved according to the results of Pre Test with the average scores of the students’ self-confidence of 56.4 and categorized as low self-confidence. (2) The assertive training method was used in one cycle which had been divided into four activities, such as case study, group discussion, role playing, and worksheet filling which lead to improvement of their self-confidence. It had been proven by conducting the average scores of self-confidence Post Test of 97.2 and was categorized as low self-confidence. Keywords: assertive training; self-confidence